PEMIKIRAN IBNU QAYYIM AL-JAUZIYAH TERHADAP PARADIGMA PERUBAHAN HUKUM - Rizal Darwis (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2017)
Islamic law is believed to be a dynamic law, responsive and adaptable to the demands of change. Ibn Qayyim al-Jawziyah in his legal thought gave the widest space to the door of ijtihad in responding to change as an inevitable reality. The paradigm of change of law is inseparable from the factors of the times, places, situations, intentions and customs. The theory of law change Ibn Qayyim al-Jawziyah is a concept of renewal of Islamic legal thought. The implications of this theory to the community in order to achieve the benefit of society as the purpose of the law itself.